Pesan Komunikasi Profetik Pada Akun Instagram @triameriza - Aulia Fauziah, Sofa (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2018)
Prophetic communication is communication related to the Prophet Muhammad. saw which is full of the behavior and ethics of the Prophet in living in the world. In the Digital Era, as is the case today, the use of social media is an option in preaching, one of which is on @triameriza account. The purpose of this research is to find out prophetic communication messages on @triameriza Instagram accounts. Using a descriptive qualitative methodology, the author tries to explain and describe prophetic communication messages in the form of short videos shared by @traimeriza accounts. Based on the results of the research, it was found that the content was full of prophetic communication messages on the Instagram account @triameriza because it was sourced from the hadiths of the prophet which were basically the behavior, words or habits of the Prophet Muhammad saw. From the perspective of the pillar of prophetic communication, humanization, there is content on @triameriza account focusing on conveying Islamic teachings sourced from the Prophet Muhammad saw. In terms of liberation, @triameriza account is able to present da'wah messages based on prophetic communication messages, packaged with short but dense video content of da'wah messages. The trend side of prophetic communication messages contained in Instagram accounts @triameriza sourced from clear hadiths that are then displayed or explained well, clearly and straight forwardly, so that followers and Instagram social media users easily receive these da'wah messages. Keywords: Prophetic Communication; Dakwah; Islamic Communication